Pengaruh Arus Kas Bebas, Ukuran Perusahaan, Profitabilitas, Dan Likuiditas Terhadap Kebijakan Hutang Di Perusahaan Manufaktur Yang Telah Terdaftar Di IDX Periode 2017-2021 - Herluin Regisa Ascend; Stephana Dyah Ayu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of net cash flow, company size, profitability, and liquidity on debt policy. The population in this study are manufacturing companies listed from 2017 to 2021, totaling 142 companies. The sampling method used in this study is purposive sampling so that a research sample of 27 companies is produced each year. The research method used in this research is multiple linear regression analysis. The results showed that free cash flow and firm size had a significant positive effect, profitability had no significant negative effect, and liquidity had a significant negative effect on debt policy. For further research, it is hoped that it can expand the subject of research, not only to manufacturing companies, but also to companies such as the service industry, property industry and the financial industry, so that the population taken is more representative and the research results can be generalized to all types of industries. Management and company owners must properly consider the variables that influence them, so that the company does not experience large financial risks. Keyword: Free Cash Flow, Size, Profitability, Liquidity, Debt Policy